2014
DOI: 10.1128/aac.04066-14
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Transmission of Antibiotic Resistance in Campylobacter jejuni Biofilms by Natural Transformation

Abstract: Campylobacter jejuni is a leading food-borne pathogen, and its antibiotic resistance is of serious concern to public health worldwide. C. jejuni is naturally competent for DNA transformation and freely takes up foreign DNA harboring genetic information responsible for antibiotic resistance. In this study, we demonstrate that C. jejuni transfers antibiotic resistance genes more frequently in biofilms than in planktonic cells by natural transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 16 publications
0
49
0
4
Order By: Relevance
“…Bae et al (2014), reported that once C. jejuni develops resistance to antibiotics, those genetic determinants can be transferred in planktonic cultures, but are most efficiently transmitted in biofilms. C. jejuni exhibits donor restriction by an unknown mechanism as it takes up free DNA from C. jejuni more readily than it does from other bacterial strains (Wang and Taylor, 1990).…”
Section: Antibiotic Resistance Determinants In Campylobactermentioning
confidence: 99%
“…Bae et al (2014), reported that once C. jejuni develops resistance to antibiotics, those genetic determinants can be transferred in planktonic cultures, but are most efficiently transmitted in biofilms. C. jejuni exhibits donor restriction by an unknown mechanism as it takes up free DNA from C. jejuni more readily than it does from other bacterial strains (Wang and Taylor, 1990).…”
Section: Antibiotic Resistance Determinants In Campylobactermentioning
confidence: 99%
“…A biofilm is a spatially organized structure, usually composed of one or more species of microorganisms [Bae et al, 2014]. Biofilm formation is influenced by many factors, including QS, the presence of flagella and specific surface proteins, substrate composition, and physicochemical properties of both cells and the substrate [Turonova et al, 2015].…”
Section: Qs and Biofilm Formationmentioning
confidence: 99%
“…Já o DNA extracelular (DNAe) e a proteína de ligação ao DNA são considerados imprescindíveis para o desenvolvimento da estrutura, pois são necessários para a formação adequada das micro colônias (SVENSSON et al, 2014), além de contribuir para o estabelecimento e a manutenção do biofilme (BAE et al, 2014, SVENSSON et al, 2014.…”
Section: Biofilmesunclassified
“…Esta característica compromete significativamente a eficácia da antibioticoterapia para o tratamento da campilobacteriose humana e resulta em desfechos adversos para o paciente, contribuindo assim, para o surgimento de infecções multirresistentes (HELMS et al, 2005;BAE et al, 2014). Há preocupação de que o tratamento da campilobacteriose humana fique comprometido em virtude da indisponibilidade de medicamentos eficazes para a terapêutica de infecções graves (EFSA, 2015b).…”
Section: Resistência Aos Antimicrobianosunclassified
See 1 more Smart Citation